RANCANG BANGUN APLIKASI E-VOTING DI SMK NURUL HUDA PETIR BERBASIS WEB DENGAN SENSOR RADIO FREQUENCY IDENTIFICATION (RFID) - R Kania; Waliadi Gunawan; Asep Saepulloh; Tifani Intan Solihati; Achmad Bisri (Journal of Innovation And Future Technology (IFTECH), 2024)
Information technology is developing rapidly in all aspects of life and until now its application has created conditions conducive to community work. One of the activities that can now take advantage of information technology is e-voting in the election of the chairman and deputy chairman of the organization. SMK Nurul Huda Petir has more than 200 students. The democratic process of selecting the head of this school organization is still used manually. There will be many obstacles, namely data security risks, which will reduce learning time, and require large implementation costs. The problems that arose created an information system called e-voting. E-voting is a system for creating ballots, casting, counting, and displaying ballot results, and generating and maintaining audit trails electronically and digitally. This research aims to speed up, improve security, and reduce implementation costs in the process of election activities at Nurul Huda Petir Vocational School. The application development process-voting uses the method Waterfall with Unified Modelling Language (UML) for system design. System e-voting its build-based web with Framework Codeigniter and added an RFID sensor (Radio Frequency Identification). The results of this research found that the application of e-voting can reduce 80% of implementation costs, improve voice data security, and speed up the process of collecting and calculating voice data.